2017
DOI: 10.1016/j.ienj.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycaemia and brief interventions in the emergency department – A systematic review

Abstract: The literature review demonstrated a lack of evidence related to BI in diabetes within the emergency setting despite the ED being an ideal environment. Future research needs to be conducted to investigate the effectiveness of BI for patients with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Findings from a meta-analysis indicated that social support from family members is significantly correlated with diabetes self-care, notably for glucose monitoring [28]. However, a recently published systematic literature review highlighted the lack of evidence related to brief interventions in diabetes and especially in the brief opportunistic environments of ED where people with diabetes attend frequently [29].…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
“…Findings from a meta-analysis indicated that social support from family members is significantly correlated with diabetes self-care, notably for glucose monitoring [28]. However, a recently published systematic literature review highlighted the lack of evidence related to brief interventions in diabetes and especially in the brief opportunistic environments of ED where people with diabetes attend frequently [29].…”
Section: Implications For Practice and Researchmentioning
confidence: 99%